Education on periodontitis prevention in pregnant women with and without orthodontic brackets [Edukasi pencegahan periodontitis pada ibu hamil pengguna bracket ortodonti dan non-bracket] - Lila Muntadir; Evi Rinata; Tontowi Ashari; Eka Setyawardana; Dini Ayu Puspitasari; Nabila Fatya Tsabita (Buletin Pengabdian Bulletin of Community Services, 2025)
The risk of periodontitis is greater in pregnant women with malocclusion, especially if they use fixed orthodontic appliances (brackets) because it is difficult to maintain oral hygiene. Untreated periodontal infection can trigger systemic inflammation and the production of pro-inflammatory cytokines, which have an impact on uterine contractions and fetal growth, and increase the risk of premature birth and low birth weight (LBW). The purpose of this community services is to carry out preventive educational efforts on the risk of periodontitis in pregnant women with malocclusion at the Sedati Health Center, both those undergoing orthodontic treatment and those not. This community services method is through interactive education, clinical examinations and facial profile photos, oral cavity to 51 pregnant women with malocclusion who undergo routine examinations at the Sedati Health Center. Interactive education by providing question and answer sheets, clinical examinations including gingival sulcus, gingival recession, periodontal exudate, tartar, tooth mobility and taking photos of the face and oral cavity profile. Result, all pregnant women do not understand periodontitis and its risks, pregnant women who use brackets have a higher percentage of pus/periodontal exudate indicators (10%) and loose teeth (30%) compared to those who do not use brackets. Pregnant women without brackets show a higher prevalence of gingival recession (19.5%) and tartar (97.6%). Conclusion, preventive education is needed comprehensively for pregnant women with malocclusion, both those who use brackets and those who do not, in order to reduce the risk of periodontitis which can have an impact on pregnancy complications.